On the Limitation of the Identification of Non-genetic Inheritors from the First Case of Applying for Cancellation of "Non-legacy" in Beijingour - Fu, Xiaoxi (Transactions on Social Science, Education and Humanities Research, 2023)
Intangible cultural heritage is the precious wealth of Chinese national spirit, which must be preserved and disseminated reasonably. The confirmation of non-genetic inheritors is one of the key links in the preservation of intangible cultural heritage. Taking the first application for cancellation of intangible cultural heritage in Beijing as an example, this paper discusses the blind area of the review mechanism identified by non-genetic inheritors, the authority and binding restrictions of the identification, understands the limitations of the identification of intangible cultural heritage, and puts forward corresponding improvement and perfection measures to promote the protection and inheritance of intangible cultural heritage.